THE EFFECT OF ROTATION AUDITS ON AUDIT QUALITY WITH AUDIT FEE AS A MODERATION - Nining Suryani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Empirically, this study aims to determine the effect of rotation audits on audit quality with audit fees as moderating manufacturing companies listed on the Indonesia Stock Exchange in 2012-2016. The population in this study are manufacturing companies listed on the Stock Exchange in 2012-2016. The sampling technique in this study used a purposive sampling technique, sampled were 24 companies with a research period of 5 years, to obtain 120 research samples. The hypothesis test uses logistic regression analysis and the moderating variable test uses Moderated Regression Analysis. The results show that the rotation audit variable doesn’t significant on audit quality, the audit fee variable has a significant effect on audit quality, while audit fees cannot moderate the effect of rotational audits on audit quality. According to the research results obtained in the F test, the rotation audit and audit fee as moderating simultaneously have a significant effect on audit quality